A path to the future, or ambivalent payoffs: tragic complexity, or a foundation for good order?. Issue 3 (1st September 2020) - O'Brien, John
ABSTRACT: Rosa's concept of 'resonance' requires greater consideration of the tensions, traps and payoffs that will result from the political programmes and institutions that will have to be developed if the concept is to be protected and promoted. The paper points out the sacrifices of ideals and resort to power and coercion that tends to come with institution building and political action, and that can warp to absurdity foundational radiant ideals. Lessons from past attempts at re-charismatisation need to be incorporated into resonance theory through a fuller historical sociological account of comparable historical movements to promote ethical ideals. .